Budaya modern mengalami perkemba Reinterpretasi Adab Jawa Dalam Karya Seni Lukis: Perspektif Generasi Z dan Alpha: Adab Jawa Dalam Karya Seni Lukis: Perspektif Generasi Z dan Alpha - Hafidh Nur Alfarizi; Amir Gozali (Warna Komunikasi, 2025)
This article highlights significant changes in Javanese society, particularly among Generation Z and Alpha, who are increasingly distancing themselves from traditional cultural values due to the influence of modern culture. In this context, the author created a painting titled "Reinterpretation of Javanese Culture in Painting: Perspectives of Generations Z and Alpha" with the aim of exploring and reinterpreting Javanese culture, using an interdisciplinary approach that links the cultural values of the past with the realities of today's younger generation, represented by traditional batik motifs combined with Lego robot action figures in a decorative style, using the sungging technique for visualization, thus creating a work that has new and more meaningful values. The creation method used refers to L.H. Chapman, encompassing three stages: 1) the emergence of an idea; 2) elaboration; 3) visualization. The resulting work, titled "Pembelajaran" (Learning) (2024), uses acrylic paint on a 100 x 120 cm canvas. It is hoped that this work can inspire and raise awareness about the importance of preserving local cultural heritage amid the highly dynamic currents of technological and social change.